Accumulation and distribution of microplastics in the sediment and coastal water samples of Chabahar Bay in the Oman Sea, Iran. (November 2020) - Hosseini, Razieh; Sayadi, Mohammad Hossein; Aazami, Jaber; Savabieasfehani, Mozhgan
Abstract: Frequency, distribution, color, and types of microplastics (<5 mm) in water and sediment of Chabahar Bay in southeastern Iran was investigated in 10 stations. Density of microplastics in water samples was between 86 and 362 particles/L (average density 218 ± 17 particle/L). In the sediment, microplastic density was between 112 and 468 particles/L (average density of 262 ± 17 particle/kg). The highest concentrations of microplastics were in stations adjacent to urban, commercial, recreational, and fishing sites. The most abundant forms in surface water and sediment were fragments (42.34%) and fibers (32.22%). Highest frequency colors were black, transparent, and white, respectively. A fourier transform infrared (FT-IR) spectrometer was used to determine micro plastic composition. Polyethylene, polyethylene terephthalate and nylon were detected. Polyethylene, a common packaging material made up 38% of the total polymers. Polyethylene terephthalate, used in clothing, liquid and food containers was found at 29% of the total microplastics. Highlights: Levels of microplastics in sediment and water of Chabahar Bay were investigated. Fragments and fibers were most common in water and sediment. <1 mm microplastics, had highest percentage in water and sediment. Polyethylene, polyethylene terephthalate and nylon were most abundant in Chabahar.